2003
DOI: 10.1002/pon.751
|View full text |Cite
|
Sign up to set email alerts
|

Coping after cancer: Risk perceptions, worry, and health behaviors among colorectal cancer survivors

Abstract: This study asks whether the experience of cancer motivates healthy behavior change. Further, we asked whether such changes relate to risk perceptions and worry, as suggested by Leventhal's Parallel Processing Model. Male (n=41) and female (n=40) survivors of colorectal cancer were interviewed 1-14 years after they first completed treatment. Younger age was associated with stronger risk perceptions, more worry, and greater anxiety. Shorter-term, compared to longer-term survivors, reported higher risk perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
147
3
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(163 citation statements)
references
References 25 publications
10
147
3
3
Order By: Relevance
“…Compared to breast cancer survivors, colorectal cancer survivors have been an understudied group, and not much research exists on colorectal cancer and dietary changes [5,6]. Some recent studies of colorectal cancer survivors show results similar to those found among breast cancer survivors [6][7][8][9].…”
Section: Introductionmentioning
confidence: 88%
“…Compared to breast cancer survivors, colorectal cancer survivors have been an understudied group, and not much research exists on colorectal cancer and dietary changes [5,6]. Some recent studies of colorectal cancer survivors show results similar to those found among breast cancer survivors [6][7][8][9].…”
Section: Introductionmentioning
confidence: 88%
“…Tsunoda et al [2] found a prevalence of 7.8% for anxiety and 36.7% for depression in ambulatory CRC patients in Japan. People with CRC may experience worry, concerns about recurrence, and high anxiety at particular times, especially right after diagnosis, when treatment begins, and when treatment ends [25]. There is an anticipatory anxiety and social embarrassment about acute and chronic diarrhea and fecal incontinence [26].…”
mentioning
confidence: 98%
“…The number of people who live with the aftereffects of cancer and its treatment-disability, fear of recurrence, and economic burden-is growing (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Factors related to suicide include mainly clinical characteristics such as age at diagnosis (6,21), prognosis (5), psychiatric status (21,22), stage (1,3,6), time since diagnosis (1,6,21), and period of diagnosis (1,(4)(5)(6), and sociodemographic characteristics such as sex (1,3), race (1,21), and marital status (1,3,21).…”
Section: Introductionmentioning
confidence: 99%